2011
DOI: 10.1080/15305058.2011.570884
|View full text |Cite
|
Sign up to set email alerts
|

Low-Stakes Testing and Psychological Reactance: Using the Hong Psychological Reactance Scale to Better Understand Compliant and Non-Compliant Examinees

Abstract: The current study examined whether psychological reactance differs across compliant and non-compliant examinees. Given the lack of consensus regarding the factor structure and scoring of the Hong Psychological Reactance Scale (HPRS), its factor structure was evaluated and subsequently tested for measurement invariance (configural, metric, and scalar) across two types of examinees: examinees that attended university assessments (i.e., compliant examinees) and examinees that skipped these assessments (i.e., non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A. R. Brown and Finney () recently explored the impact of noncompliance on test scores at their home university, where all first‐year students are required to take a 3‐hour assessment that measures general education skills. They are also required to take the same tests in their second or third year so that growth can be determined.…”
Section: Individual Difference Predictors and Indicators Of Low Motivmentioning
confidence: 99%
See 3 more Smart Citations
“…A. R. Brown and Finney () recently explored the impact of noncompliance on test scores at their home university, where all first‐year students are required to take a 3‐hour assessment that measures general education skills. They are also required to take the same tests in their second or third year so that growth can be determined.…”
Section: Individual Difference Predictors and Indicators Of Low Motivmentioning
confidence: 99%
“…The researchers tested the hypothesis that students who do not attend the original testing session are more reactant than compliant examinees. Reactance refers to a reaction to threats to perceived loss of freedoms (Brehm & Brehm, 1981). Noncompliance is a common response to feelings of reactance (Brehm & Brehm, 1981).…”
Section: Noncompliancementioning
confidence: 99%
See 2 more Smart Citations
“…Test-takers who were less compliant, that is, less motivated, to take the test tended to show higher levels of reactance (Brown and Finney 2011). Another line of research has shown that boredom negatively affects test-taking effort (e.g., Asseburg and Frey 2013).…”
Section: Person Levelmentioning
confidence: 99%